MOTS-c and its K14Q variant demonstrate significant lipid-lowering and weight-reducing effects in obese mice: Lipid and weight effects of MOTS-c K14Q (Indian Journal of Experimental Biology (IJEB), 2026)
A 1382A>C substitution in the MOTS-c gene results in a K14Q amino acid replacement. Research on the MOTS-c K14Q variant is still limited, and its role in blood lipid metabolism remains unclear. In this study, we investigated the effects of MOTS-c and its K14Q variant on obesity. A diet-induced obesity mouse model was established and treated with injections of either MOTS-c or the K14Q variant. Subsequent analyses examined AMPK (PRKAA1) expression, changes in body weight, and serum lipid profiles, including total cholesterol (TC), triglycerides (TG), and free fatty acids (FFA). Both MOTS-c and the K14Q variant activated AMPK expression and reduced body weight as well as levels of TC, TG, and FFA. However, MOTS-c exhibited a stronger effect on reducing TC and TG, whereas the K14Q variant showed a greater impact on lowering FFA. In conclusion, MOTS-c and its K14Q variant both exert lipid-lowering effects, but their differential impacts on TC, TG, and FFA suggest distinct regulatory roles in blood lipid metabolism.